Nano-contact microscopy of supracrystals - Sweetman, Adam; Goubet, Nicolas; Lekkas, I.; Pileni, Marie Paule; Moriarty, Philip (Bellstein-Institut, 2015)
Background: Highly ordered three-dimensional colloidal crystals (supracrystals) comprised of 7.4 nm diameter Au nanocrystals (with a 5% size dispersion) have been imaged and analysed using a combination of scanning tunnelling microscopy and dynamic force microscopy.